Impacts of Family Tourism on the families’ Quality of Life – differences according to the family economic profile - Lima, Joana (2019)
Tourism plays a significant role in our lives and is increasingly becoming associated with Quality of Life (QOL). Tourism offers opportunities to explore new environments, participate in new activities and to meet people as well as relax. While the effects of tourism on the QOL of individuals are nowadays recognized, the effects of family tourism upon families’ QOL are relatively blurred. This neglect is more worrying insofar as it is known that family tourism represents a significant share in the tourism market globally. This study aims to overcome this gap by analysing the effects of family tourism on some dimensions of families’ QOL, using survey data collected from a sample of Portuguese families (N = 825). Moreover, we explore whether the impacts of family tourism on families’ QOL vary across the economic profile of families. This study is of utmost relevance given that families with low income represent a significant share of the Portuguese population nowadays. The results reveal significant effects of family tourism on family cohesion and on the improvement of families’ QOL. The effects differ between families, with families with scarce economic resources being those that feel the effects with greater intensity. The chapter concludes with a discussion on the implications of the results for the design of family tourism experiences and also identifying paths for future research.